Insights on social equity and climate adaptation from low-income rural Filipinos - Petesch, Patti; Fisher, Eleanor; Echavez, Chona; Hellin, Jon; Montejo, Michael Lou; Rockwell, Perry Henry; Salcedo, Sonica; Ebenstål Almeida, Olivia (International Rice Research Institute, 2025)
Policies and programs that nurture social equity will be vital for effective responses to climate change, but little is known about actions that will be both equitable and reliably strengthen capacity for climate adaptation on the ground. Indeed, climate-related interventions continue to run risks of harm to disadvantaged and vulnerable populations, and most especially to those already enduring severe and accelerating climate crises. This research brief explores these urgent challenges through testimonies shared during focus groups with low-income women and men in the Philippines, who reside in vulnerable coastal and highland areas that are greatly affected by climate change. They mostly associate social equity with notions of equality; namely that all should be treated equally whether interacting socially or distributing resources. Most study participants express discouragement about their capacity to adapt their farming, livestock, and fishing livelihoods to climate risks. Yet, women as well as men also reveal certain practices that help to equip them for typhoons, droughts and prolonged periods of seasonal scarcity. Their testimonies about these climate-related practices convey a “can-do” quality, along with locational, gendered, climate-resilient, and reliable income-generation aspects. As this research demonstrates, these qualities present both risks and opportunities, and offer lessons for policies and programs aiming to advance equitable adaptation capacity in the Philippines. Such policies include The National Climate Change Action Plan (NCCAP) 2011-2028, and the Climate Change Act of 2009 (RA 9729). Participatory action learning approaches work to maximize the opportunities and minimize the risks because they are locally led and—with facilitation support and other resources of external partners—grounded in the knowledge and experiences of what works according to poor and marginalized women and men on the frontlines of climate change.